2022
DOI: 10.1149/1945-7111/aca050
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered (Fe,Mn)3O4 Spinel Oxide Thin Films for Micro-Supercapacitor

Abstract: The scaling up of wireless operating microelectronics for upcoming Internet of Things (IoT) applications demands high-performance micro-supercapacitors (MSCs) with corresponding high-energy and power capabilities. Indeed, this necessitates the quest for MSC’s electrode materials capable of delivering high energy density at high charge/discharge rates. Many multicationic oxides, such as spinel manganese-iron compounds, demonstrate good pseudocapacitive properties as positive electrodes in conventional supercapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…96 Recent research has shown that Mn-based spinels, particularly MnFe 2 O 4 , demonstrate a wide working potential range in an aqueous medium and a pseudocapacitance mechanism close to that of MnO 2 , suggesting favorable properties for both highenergy and power applications. 51,93,94 Sputtered TiVN ternary films were also investigated as an electrode for MSC and exhibit a surface capacitance value of 15 mF cm −2 in KOH aqueous electrolyte. 97 MXenes, 36,98,99 the family of early transition metal carbides, nitrides, or carbonitrides, have also been widely investigated as efficient electrodes, due to the high rate/high capacitance properties issued from their two-dimensional properties.…”
Section: Emerging Materials For Designing Efficient Electrodes For Mscsmentioning
confidence: 99%
See 3 more Smart Citations
“…96 Recent research has shown that Mn-based spinels, particularly MnFe 2 O 4 , demonstrate a wide working potential range in an aqueous medium and a pseudocapacitance mechanism close to that of MnO 2 , suggesting favorable properties for both highenergy and power applications. 51,93,94 Sputtered TiVN ternary films were also investigated as an electrode for MSC and exhibit a surface capacitance value of 15 mF cm −2 in KOH aqueous electrolyte. 97 MXenes, 36,98,99 the family of early transition metal carbides, nitrides, or carbonitrides, have also been widely investigated as efficient electrodes, due to the high rate/high capacitance properties issued from their two-dimensional properties.…”
Section: Emerging Materials For Designing Efficient Electrodes For Mscsmentioning
confidence: 99%
“…Recent research has shown that Mn-based spinels, particularly MnFe 2 O 4 , demonstrate a wide working potential range in an aqueous medium and a pseudocapacitance mechanism close to that of MnO 2 , suggesting favorable properties for both high-energy and power applications. ,, Sputtered TiVN ternary films were also investigated as an electrode for MSC and exhibit a surface capacitance value of 15 mF cm –2 in KOH aqueous electrolyte …”
Section: Emerging Materials For Designing Efficient Electrodes For Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their film exhibited 15.5 mF• cm −2 (155 F•cm −3 ) of capacitance and stability after 10,000 cycles. 20 Besides the trial-and-error method, the predictive approach using DFT (density-functional theory) theoretical calculations is nowadays a very interesting approach to discovering new materials. In that context, since our group had some experience in the synthesis of metal nitrides compounds, 11,12 we decided to follow the extensive work of Sun et al 21 who have systematically mapped predicted inorganic ternary nitrides (i.e., multicationic compounds).…”
Section: ■ Introductionmentioning
confidence: 99%